Cultural Dimensions of Stroking Behavior: A Comparative Analysis of Persian and English Communication in Media Contexts - Zahra Ghadamyari; Haniyeh Jajarmi (Media and Intercultural Communication: A Multidisciplinary Journal)
In the realm of intercultural communication, effective interaction surpasses mere language proficiency, an understanding of the culture of a society is equally vital. Aiming to unravel the cultural perspectives of two distinct societies, this research examined the cultuling of stroking behavior in Persian and English languages steered by the conceptual model of cultuling analysis (CLA). To this end, 30 randomly selected Persian and English movies from various genres spanning the past decade served as the medium for data collection. A total of 306 speech segments embracing the cultuling of stroking behavior were extracted to the saturation level and examined based on the CLA model. The findings shed light on diverse hidden cultural patterns of Persian speakers in contrast to those of English speakers encompassing collectivism, indirectness, power distance, high context, low trust, and high waitance. Finally, the factors contributing to these differences are discussed and the implications of the study and suggestions for further research are presented.